Contesting digital leisure time: Parental struggles in relation to young children's play with tablets at home - Lundtofte Thomas Enemark (Nordicom Review)
Young children's practices with tablet computers has been a topic in parenting discourses for several years, drawing on earlier debates over technologies and media in children's lives. In this article, I analyse data from a video observation–based media ethnography of seven Danish children (aged 4–6) and engage with the research tradition attributed to parental mediation. The analysis suggests two major paths in the struggles that stand out from the discourses and in situ practices of parents and children in the empirical data. These paths encompass struggles in relation to supporting and directing children's play activities and setting boundaries in their use of tablets and content. The nuances and implications of both paths are analysed and discussed in terms of strategies that emerge to support children's agency and rapport with parents, as well as what this means for future research.